Brain-Predicted Age Difference Moderates the Association Between Muscle Strength and Mobility - Vaughan, Brooke A.; Simon, Janet E.; Grooms, Dustin R.; Clark, Leatha A.; Wages, Nathan P.; Clark, Brian C. (Frontiers in Aging Neuroscience, 2022)
Background Approximately 35% of individuals over age 70 report difficulty with mobility. Muscle weakness has been demonstrated to be one contributor to mobility limitations in older adults. The purpose of this study was to examine the moderating effect of brain predicted age difference, an index of biological brain age based on structural neuroimaging, on the relationship between leg strength and mobility. Methods In community dwelling adults (N=57, 74.7 ± 6.93 yrs; 68% women), we assessed the relationship between isokinetic leg extensor strength and a composite measure of mobility (mobility battery assessment [MBA]) using partial Pearson correlations and multifactorial regression modeling. Brain predicted age (BPA) was calculated from T1 MR-images using a validated machine learning Gaussian Process regression model to explore the moderating effect of BPA difference (BPAD; BPA minus chronological age). Results Leg strength was significantly correlated with BPAD (r = -0.317, p < .05) and MBA score (r = 0.541, p < .001). Chronological age, sex, leg strength and BPAD explained 63% of the variance in MBA performance (p <0.001). BPAD was a significant moderator of the relationship between strength and MBA, accounting for 7.0% of MBA score variance (∆R2 = 0.044, F(1, 51) = 6.83, p = 0.01). Conditional moderation effects of BPAD indicate strength was a stronger predictor of mobility in those with a great BPAD. Conclusion The relationship between strength and mobility appears to be influenced by brain aging, with strength serving as a possible compensation for decline in neural integrity.